Corruption and Firms - Emanuele Colonnelli; Mounu Prem (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2019)
We estimate the causal real economic effects of a randomized anticorruption crackdown on local governments in Brazil over the period 2003-2014. After anti-corruption audits, municipalities experience an increase in economic activity concentrated in sectors most dependent on government relationships. These effects spill over to nearby municipalities and are larger when the audits are covered by the media. Back-of-the-envelope estimates suggest that 1 away from corruption generates more than 3 in local value added. Using administrative matched employer-employee and firm-level datasets and novel face-to-face firm surveys we argue that corruption mostly acts as a barrier to entry, and by introducing costs and distortions on local government-dependent firms. The political misallocation of resources across firms plays a seemingly secondary role, indicating that at the local level most rents are captured by politicians and public officials rather than firms.
Keywords: 330; Anti-Korruption; Wirkungsanalyse; Unternehmen; Kommunale Entwicklung; Regionalentwicklung; Schätzung; Brasilien